2006
DOI: 10.1111/j.1742-7843.2006.pto_193.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Symptoms Associated with Statins: A Series of Twenty Patients

Abstract: The aim of this study was to examine the clinical profile of statin-induced myalgia in patients with no apparent predisposing factors. Patients who reported muscle complaints that limited daily functioning during statin use were prospectively identified among the patients of Kuusankoski District Hospital and its catchment area, a population of about 100,000, between January 2003 and July 2004. Twenty patients in whom the muscle complaints were probably attributable to the use of a statin were included in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…b Creatine kinase tends to be in the very high range, from 3000-25000 IU/L, with a mean of 12900 IU/L [3]. In statin-related NAM, the creatine kinase has also been found in the high range of 958-45000 U/L [24], with the majority between 3000-8000 U/L, compared with likely a lower creatine kinase level of less than 2000 U/L in those with the self-limited toxic myopathy [23].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…b Creatine kinase tends to be in the very high range, from 3000-25000 IU/L, with a mean of 12900 IU/L [3]. In statin-related NAM, the creatine kinase has also been found in the high range of 958-45000 U/L [24], with the majority between 3000-8000 U/L, compared with likely a lower creatine kinase level of less than 2000 U/L in those with the self-limited toxic myopathy [23].…”
Section: Treatmentmentioning
confidence: 99%
“…NAM associated with statins is presumed to have an immunological basis, different from the toxic myopathy found in most statin-associated myopathies which is selflimited and recovers over weeks to months upon discontinuation of the statin [23,24]. Two studies [2 ,24] reported a series of patients in whom there was active myocyte necrosis, mostly with minor or absent inflammation, in whom the myopathy persisted or progressed despite cessation of the statin.…”
Section: Statin-triggered Autoimmunitymentioning
confidence: 99%
“…Specifically, the READ classification does not necessarily correspond to disease entities, and additional work was necessary to define criteria for classes of adverse events such as myopathy, myalgia and myositis which were included in the analyses. Additionally we selected READ codes for creatinine kinase measurements and included cases who had elevations at >10 times the upper limit of normal 100 IU/ml in females and 150 IU/ml in males, although not all patients with myopathy have elevated CK values [21]. Codes included identifying co-morbidities and potential confounders (for example cases with codes for rheumatic diseases and steroid use were excluded).…”
Section: Methodsmentioning
confidence: 99%
“…Although the vast majority of statin-associated myopathies resolve upon drug cessation [53,54], there is increasing recognition that in some cases muscle symptoms can persist or progress [55•, 56•, 57, 58]. These cases seem to fall into two categories.…”
Section: Immune-mediated Myopathiesmentioning
confidence: 99%